Factors associated with real‐time RT‐PCR cycle threshold values among medically attended influenza episodes. Issue 4 (21st September 2015) - Spencer, Sarah; Chung, Jessie; Thompson, Mark; Piedra, Pedro A.; Jewell, Alan; Avadhanula, Vasanthi; Mei, Minghua; Jackson, Michael L.; Meece, Jennifer; Sundaram, Maria; Belongia, Edward A.; Cross, Rachel; et al.
Abstract : We evaluated the cycle threshold (CT) values of 1, 160 influenza A positive and 806 influenza B positive specimens from two seasons of the US Flu VE Network to identify factors associated with CT values. Low CT values (high genomic load) were associated with shorter intervals between illness onset and specimen collection, young age (ages 3–8 years old), and self‐rated illness severity for both influenza A and B. Low CT values were also associated with reported fever/feverishness and age ≥65 years for influenza A. J. Med. Virol. 88:719–723, 2016 . © 2015 Wiley Periodicals, Inc.